Anatomedia a new approach to medical education development in anatomy - Anatomedia Pty Ltd; Anatomedia Pty Ltd (Melbourne : Anatomedia Pty Ltd., 2002)
Anatomedia is a unique way to learn about the anatomy of the human body. It allows you to'construct' the body by studying regions and systems and to'deconstruct' the body through dissection and imaging
Modules : back, abdomen and thorax
Macintosh: any power Macintosh (G3 recommended) ; 32MB RAM ; MacOS 7.6.1 or higher ; quad speed pr faster CD-ROM drive ; 2MB video card capable of displaying 800*600 in 16-bit colour quick time 3.0 or higher (installer for quick time included)
Keywords: Human, Anatomy